Pengaruh Motivasi Belajar terhadap Prestasi Belajar IPS Siswa Kelas VI di UPTD SD Negeri 122348 Pematangsiantar - Agnes Chintya Dewi; Lisbet N. Sihombing; Hetdy Sitio (Medan Resource Center, 2022)
The Influence of Motivation on Social Studies Learning Achievement of Class VI Students at UPTD SD Negeri 122348 Pematangsiantar. Thesis. UHKBPNP University Primary School Teacher Education and Education Studies Program. Advisor I Lisbet Novianti Sihombing,S.Pd.,M.Pd and Advisor II Hetdy Sitio M.Pd. This study aims to determine whether there are. The Influence of Motivation on Social Studies Learning Achievement of Grade VI Students at UPTD SD Negeri 122348 Pematangsiantar. This study aims to determine the description of the social studies learning motivation of grade VI students and how much influence the social studies learning motivation of students at UPTD SD Negeri 122348. This study is a quantitative method, with the entire research population. class VI students totaling 33 people. The results showed that the description of the social studies learning motivation of students at UPTD SD Negeri 122348 Pematangsiantar was in the high category, namely 87% of the social studies learning achievement of students and the influence of social studies learning motivation.